2021
DOI: 10.3389/fpsyt.2021.618993
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of COVID-19 Pandemic Among the General Population in Jordan

Abstract: Objective: Pandemics are claimed to result in certain stressors. However, the potential psychological impact of a pandemic is often overlooked. The current study aimed to assess the psychological impact of the COVID-19 pandemic on Jordanians and to evaluate the influence of the socio-demographic variables on this impact.Method: The current study employed a descriptive cross-sectional design using the Impact of Event Scale—Revised (IES-R) via a web-based questionnaire. The researchers utilized convenience sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 35 publications
3
31
1
Order By: Relevance
“…Consequently, this led to the overwhelming of both the healthcare system and the health workforce. Besides, the pandemic existence in the country has imposed significant psychosocial and health impacts on HCWs and various components of the society as well [4,12,[21][22][23][24][25][26]. In addition, various changes have affected health services delivery in response to the repercussions of the pandemic and its mitigation measures in Jordan, and this may exhibit unprecedented effects on the HCWs [12,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this led to the overwhelming of both the healthcare system and the health workforce. Besides, the pandemic existence in the country has imposed significant psychosocial and health impacts on HCWs and various components of the society as well [4,12,[21][22][23][24][25][26]. In addition, various changes have affected health services delivery in response to the repercussions of the pandemic and its mitigation measures in Jordan, and this may exhibit unprecedented effects on the HCWs [12,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a recently published study in China did not report any significant association between the prevalence of anxiety symptoms and different occupational groups. 22 However, a study conducted in Jordan reported higher anxiety scores in older age, 26 whereas, studies conducted in Iran 13 and China 22 reported that younger people tend to experience anxiety symptoms more than older participants.…”
Section: Discussionmentioning
confidence: 97%
“…The reasons behind males' vulnerability for worse outcomes might include immune-suppressive effects of testosterone, higher smoking rates, and higher rates of respiratory tract infections among males ( 31 ). Nevertheless, psychological distress and anxiety were reported to be higher among Jordanian females during the pandemic crisis ( 17 , 32 ), and this may play a vital role in the vulnerability of females to contract COVID-19 infection, considering the proven link between psychological stressors and their negative impact on immune system's defense mechanisms against viral infections ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…This social adjacency of Jordanians, along with the flattened epidemic curve, encouraged authorities to alleviate lockdown measures and encouraged people to adopt less strict preventive measures. As a result of this alleviation, Jordan changed from a role model in combating the pandemic to one of the most impacted countries with a severe physical and psychological burden (16)(17)(18). According to Jordan's MoH data, more than 803 351 cases were confirmed across the country as of 07 September 2021 (19).…”
Section: Introductionmentioning
confidence: 99%